2016
DOI: 10.1111/tbed.12551
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Natural Infections in Sheep/Goats with HoBi-like Pestiviruses in China

Abstract: The natural infections of HoBi-like pestiviruses in cattle have been reported in South America, Europe and Asia. In China, although the detections of HoBi-like pestivirus have been reported, the epidemiological investigation was limited. From January 2014 to October 2015, several flocks of sheep/goats in Henan province in central China suffered respiratory diseases which were recovered slowly after antibiotics treatment. To test whether it is the HoBi-like pestivirus caused this symptom, 49 serum samples and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The phylogenetic tree obtained for the 5′UTR (Figure a) showed three well‐separated clusters corresponding to HoBi‐like viruses genetic groups a, c and d. All of the sequences obtained in this work were grouped into the genetic group “a” cluster. This cluster presented three branches corresponding to Th/04KhonKaen (GenBank accession number ) detected in Thailand (Ståhl et al., ); HN1507 (GenBank accession number ) detected in China (Shi et al., ); and the last branch contained strains detected in South America, Europe and China, as well as all the sequences reported herein. In general, the sequences obtained in this study were more closely related to previously reported strains than to each other.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…The phylogenetic tree obtained for the 5′UTR (Figure a) showed three well‐separated clusters corresponding to HoBi‐like viruses genetic groups a, c and d. All of the sequences obtained in this work were grouped into the genetic group “a” cluster. This cluster presented three branches corresponding to Th/04KhonKaen (GenBank accession number ) detected in Thailand (Ståhl et al., ); HN1507 (GenBank accession number ) detected in China (Shi et al., ); and the last branch contained strains detected in South America, Europe and China, as well as all the sequences reported herein. In general, the sequences obtained in this study were more closely related to previously reported strains than to each other.…”
Section: Resultsmentioning
confidence: 75%
“…The frequencies of active infections reported in this study were similar to a previous study conducted in Southern Brazil that found 0.36% pestivirus‐positive calves (Weber et al., ); however, the infection frequencies reported in the present study were lower than the 2.8% frequency reported in Belgium (Hanon et al., ). None of the small ruminant samples tested positive for pestivirus infection despite reports of natural infection of small ruminants with the bovine pestiviruses: BVDV‐1, BVDV‐2 and HoBi‐like viruses (Han et al., ; Kim et al., ; Shi et al., ; Vilcek, Nettleton, Paton, & Bélak, ).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations